2017
DOI: 10.1002/mar.21039
|View full text |Cite
|
Sign up to set email alerts
|

Does organizational creativity always drive market performance?

Abstract: This study develops and tests arguments that the relationship between organizational creativity and market performance is channeled through new product development (NPD) capability, and that the indirect effect of creativity on performance, via NPD capability, is conditional upon levels of environment dynamism and market responsiveness. The proposed relationships are tested on a sample of 221 small‐ and medium‐sized enterprises (SMEs) in a major sub‐Saharan African market. Findings from the study indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 63 publications
1
12
0
7
Order By: Relevance
“…The results showed that green creativity has a positive and significant effect on brand performance. This finding is consistent with Wu [26], Chen et al [23], Boso et al [41], Aeknarajindawat and Jermsittiparsert [40] and Ferreira et al [43]. To explain this finding, it can be claimed that brand performance will be improved if company employees propose new ways to achieve environmental goals, suggest new green ideas to improve environmental performance, promote new green ideas to others, develop good plans for implementing green ideas, and come up with creative solutions to environmental issues.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results showed that green creativity has a positive and significant effect on brand performance. This finding is consistent with Wu [26], Chen et al [23], Boso et al [41], Aeknarajindawat and Jermsittiparsert [40] and Ferreira et al [43]. To explain this finding, it can be claimed that brand performance will be improved if company employees propose new ways to achieve environmental goals, suggest new green ideas to improve environmental performance, promote new green ideas to others, develop good plans for implementing green ideas, and come up with creative solutions to environmental issues.…”
Section: Discussionsupporting
confidence: 78%
“…Studies that have examined the relationship between corporate social responsibility and commitment have shown that there is a positive and significant relationship between corporate social responsibility and commitment [35][36][37][38][39]. In addition, research has shown that there is a positive and significant relationship between creativity and performance [40][41][42][43][44]. Therefore, it is assumed:…”
Section: Corporate Social Responsibility Green Creativity and Performentioning
confidence: 99%
“…For instance, Khedhaouria, Gurău [ 96 ] conducted a study in French SMEs and scrutinized that creativity does not directly influence firm performance but entrepreneurial orientation fully mediates the path. Boso, Donbesuur [ 47 ] revealed that organizational creativity first configures new product development speed which in turn influences new product performance. The nation was also supported by Cheng and Yang [ 97 ] who concluded that new product development activities and speed mediate the connection between creative process and new product performance.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…With creative skills and abilities, an organization is able to develop and commercialize new products and process that are rare, unique, valuable and imperfectly imitable. These advantages (new product and new process that are gained through creativity) in turn facilitates firms in getting superior market performance and increased success [ 47 ]. Creativity significantly influences the internal process (strategy, competitive advantage and ideas) of a firms that in turn affect profitability and performance [ 42 ].…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Penelitian yang dilakukan oleh Rubera et al (2010) terhadap 283 konsumen di Milan, Italia menunjukkan bahwa untuk mengalahkan pesaing dengan kreativitas produk, industri harus mengembangkan kemampuan untuk memilih segmentasi pasar sesuai dengan tingkat kebaruan dan kesesuaian yang diwujudkan dalam produk tersebut. Penelitian lain tentang hubungan kreativitas dengan kinerja industri telah dilakukan oleh Boso et al (2017) terhadap 221 industri di Afrika. Adapun temuan yang diperoleh juga menunjukkan bahwa kreativitas berpengaruh terhadap kinerja industri.…”
Section: Pendahuluanunclassified